2017
DOI: 10.26493/1855-3974.1172.bae
|View full text |Cite
|
Sign up to set email alerts
|

On domination-type invariants of Fibonacci cubes and hypercubes

Abstract: The Fibonacci cube Γ n is the subgraph of the n-dimensional cube Q n induced by the vertices that contain no two consecutive 1s. Using integer linear programming, exact values are obtained for γ t (Γ n), n ≤ 12. Consequently, γ t (Γ n) ≤ 2F n−10 + 21F n−8 holds for n ≥ 11, where F n are the Fibonacci numbers. It is proved that if n ≥ 9, then γ t (Γ n) ≥ (F n+2 − 11)/(n − 3) − 1. Using integer linear programming exact values for the 2packing number, connected domination number, paired domination number, and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…We start by presenting some known values of these numbers in Table 1, which was given in [1,14]. Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We start by presenting some known values of these numbers in Table 1, which was given in [1,14]. Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Note that, in [1] by using integer programming it is shown that 54 ≤ γ(Γ 12 ) ≤ 61 and 97 ≤ γ t (Γ 13 ) ≤ 101.…”
Section: E Saygi / Upper Bounds On the Domination And Total Dominatimentioning
confidence: 99%
See 3 more Smart Citations